Emotional Intelligence and Its Relationship to Problem Solving among the Ajloun University- College Students - Al-Saadi, Wail Minwer (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed at determining the level of emotional intelligence and problem solving among students of the Ajloun University College, identifying the relationship between emotional intelligence and the ability to solve problems via showing the differences in the degree of emotional intelligence possession and the ability to solve problems according to gender (male and female) and academic specialization (Psychological Counselling, Special Education, and Social Service) variables. The study sample community consisted of (448) male and female students from the Faculty of Educational Sciences at Jadara University. And the study sample was represented by an accessible sample of (370) male and female students. The researcher used two instruments to achieve the objectives of the study: a sale of emotional intelligence prepared by Mazloum (2011), and another of the ability to solve problems prepared by (Hepper and Peterson, 1982), which was translated into Arabic by the researcher Al-Samadi Abdullah Abdul-Ghafour. The researcher verified their validity and reliability in multiple ways. The researcher used in his study the descriptive-analytical relational approach. The results of the study indicated that the students of the College of Educational Sciences possessed a high degree of emotional intelligence and at a statistical significance level. Unlikely, they have a low degree and statistically significant level regarding the ability to solve problems. There were positive correlations and a statistically significant relationship between emotional intelligence and the ability to solve problems. Likewise, there were statistically significant differences in the level of emotional intelligence regarding the gender variable and favour of males. However, there were no statistically significant differences in the level of ability to solve problems according to gender, having the absence of statistically significant differences in emotional intelligence and the level of ability to solve problems according to academic specialization. The results also indicated an expected ability of emotional intelligence to predict the skill of solving problems capability. The study recommended the necessity of holding seminars and workshops for university students, introducing them to the importance of emotional intelligence and its role in their lives, setting up training programs to help students raise the level of emotional intelligence, as well as developing their capabilities in solving problems